Drug Reaction, Eosinophilia and Systemic Symptoms (DRESS) syndrome secondary to allopurinol with early lymphadenopathy and symptom relapse. (5th October 2015) - Turney, Rhiannon; Skittrall, Jordan Peter; Donovan, Joseph; Agranoff, Daniel
Abstract : Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a rare condition with a mortality rate of up to 10%. Herein, we describe a case of DRESS syndrome secondary to allopurinol and which may have been precipitated by amoxicillin, the diagnostic challenge it represented and the successful treatment of the condition with corticosteroids.